Fusarium xyrophilum, sp. nov., a member of the Fusarium fujikuroi species complex recovered from pseudoflowers on yellow-eyed grass (Xyris spp.) from Guyana. (2nd January 2020) - Laraba, Imane; Kim, Hye-Seon; Proctor, Robert H.; Busman, Mark; O'Donnell, Kerry; Felker, Frederick C.; Aime, M. Catherine; Koch, Rachel A.; Wurdack, Kenneth J.
ABSTRACT: We report on the discovery and characterization of a novel Fusarium species that produced yellow-orange pseudoflowers on Xyris spp. (yellow-eyed grass; Xyridaceae) growing in the savannas of the Pakaraima Mountains of western Guyana. The petaloid fungal structures produced on infected plants mimic host flowers in gross morphology. Molecular phylogenetic analyses of full-length RPB1 (RNA polymerase largest subunit), RPB2 (RNA polymerase second largest subunit), and TEF1 (elongation factor 1-α) DNA sequences mined from genome sequences resolved the fungus, described herein as F. xyrophilum, sp. nov., as sister to F. pseudocircinatum within the African clade of the F. fujikuroi species complex. Results of a polymerase chain reaction (PCR) assay for mating type idiomorph revealed that single-conidial isolates of F. xyrophilum had only one of the MAT idiomorphs ( MAT1-1 or MAT1-2 ), which suggests that the fungus may have a heterothallic sexual reproductive mode. BLASTn searches of whole-genome sequence of three strains of F. xyrophilum indicated that it has the genetic potential to produce secondary metabolites, including phytohormones, pigments, and mycotoxins. However, a polyketide-derived pigment, 8- O -methylbostrycoidin, was the only metabolite detected in cracked maize kernel cultures. When grown on carnation leaf agar, F. xyrophilum is phenotypically distinct from other described Fusarium species in that it produces aseptate microconidia on erect indeterminate synnemata that are up to 2 mm tall and it does not produce multiseptate macroconidia.